Power Development in Maharashtra, Maharashtra Economic Development Council - Planning Commission (Planning Commission, 1957)
Human progress depends on the availability of energy and the capacity and willingness of the human beings to discover and harness the energy available in Nature. The forms in which energy is available and can be utilised are generally classified as solid, liquid, gaseous and nuclear. It is available from coal, petroleum products, natural gas, solar heat, geo-thermal heat and wind power. The use of any particular form of energy is largely a function of our knowledge in harnessing it and the costs involved. the last two hundred years have seen tremendous expansion in our knowledge and capacity to develop different forms of energy resources. Prior to that, wood, water power and wind power constituted for basic sources of energy.
Maharashtra Economic Development Council
Maharashtra Economic Development Council